2003
DOI: 10.1007/s00125-003-1226-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in skeletal muscle of non-diabetic insulin-resistant and insulin-sensitive Pima Indians by differential display PCR

Abstract: Aims/hypothesis. Whole body insulin resistance results largely from impaired insulin-stimulated glucose disposal into skeletal muscle. We carried out muscle gene expression profiling to identify differentially expressed genes associated with insulin resistance. Methods. Skeletal muscle total RNA samples from six pairs of non-diabetic insulin-resistant and insulin-sensitive Pima Indians matched for percent body fat were analyzed by DDPCR with 90 primer combinations. The mRNA expression concentrations of selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 41 publications
(31 reference statements)
0
10
1
Order By: Relevance
“…ATP1A2, which codes for an ATPase, was previously found to be differentially expressed between insulin resistant and insulin sensitive muscle tissue, though in the opposite direction than was found in this study [52]. PMP2 (Entrez Gene ID: 5375) and SRGN (5552), coding for a myelin protein and hematopoietic proteoglycan, respectively, lack any literature evidence for a relationship to IR; illumination of their specific roles would require further study.…”
Section: Discussioncontrasting
confidence: 52%
“…ATP1A2, which codes for an ATPase, was previously found to be differentially expressed between insulin resistant and insulin sensitive muscle tissue, though in the opposite direction than was found in this study [52]. PMP2 (Entrez Gene ID: 5375) and SRGN (5552), coding for a myelin protein and hematopoietic proteoglycan, respectively, lack any literature evidence for a relationship to IR; illumination of their specific roles would require further study.…”
Section: Discussioncontrasting
confidence: 52%
“…Although there was no difference in daily alcohol consumption between the groups, we found that serum GGT levels decreased in the intervention group, but increased in the control group. These findings are important, since it has been reported that the serum concentrations of GGT and ALT are a predictive marker of type 2 diabetes [30-33], even at concentrations still considered to be within the normal range [34]. Thus, the difference in the changes in GGT levels between the groups is likely to reflect changes in liver fat contents.…”
Section: Discussionmentioning
confidence: 95%
“…Lee et al [41] demonstrated moderate differential MAP2K4 expression in the skeletal muscle of six pairs of insulin-sensitive and insulin-resistant Pima Indians matched for percent body fat. NCOR1 has been shown to interact with all three forms of PPAR [42], well known candidate genes for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%